2019
DOI: 10.18699/vj19.515
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of depressive disorders

Abstract: Depression is a common mental disorder being one of the main causes of disability and mortality worldwide. Despite an intensive research during the past decades, the etiology of depressive disorders (DDs) remains incompletely understood; however, genetic factors are significantly involved in the liability to depression. The present review is focused on the studies based on a candidate gene approach, genome-wide association studies (GWAS) and whole exome sequencing (WES), which previously demonstrated associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
1
0
1
Order By: Relevance
“…Для создания модели достаточно два агрессора на 12-15 животных. Конфликтную ситуацию следует создавать несколько раз (2)(3)(4)(5)(6). Одной из модификаций является модель сенсорного контакта.…”
Section: способы моделирования депрессии у грызуновunclassified
See 1 more Smart Citation
“…Для создания модели достаточно два агрессора на 12-15 животных. Конфликтную ситуацию следует создавать несколько раз (2)(3)(4)(5)(6). Одной из модификаций является модель сенсорного контакта.…”
Section: способы моделирования депрессии у грызуновunclassified
“…Описано большое количество нейробиологических процессов, которые могут лежать в основе различных типов депрессии. Установлено и во многом изучено влияние генетических факторов на развитие заболевания [4]. Описана значительная роль травматических стрессовых событий пренатального и раннего постнатального онтогенеза при развитии депрессии.…”
Section: Introductionunclassified
“…Multiple efforts were made to unravel the hypothesis-driven [3][4][5] and/or hypothesisfree approaches [6][7][8][9][10][11] to dissect a genetic cause of depression. Existing molecular mechanisms underlying depressive pathology are based on the impaired neurotransmitter signaling [12], hypothalamic-pituitary-adrenal (HPA) axis [5], oxytocin and arginine vasopressin systems [4,13,14], inflammatory response [3,15], telomere length-associated molecular pathways [16,17], nucleotide changes in target mRNA-miRNA binding sites [18,19], etc. Genome-wide association studies (GWAS) of depression and their meta-analyses implementing a hypothesis-free approach identified multiple genetic loci [7][8][9]11,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Together with a traditional approach, the use of bioinformatic pipelines to estimate telomere length under whole-genome sequencing (TelSeq) revealed that shortening of telomeres in depressive disorders was associated with adverse environmental conditions [ 1 ]. It is known that adverse stress conditions at an early age cause a pleiotropic behavioral, physiological, and epigenetic effect on various systems of the body [ 13 ] owing to the changes in the stress response of the hypothalamic-pituitary-adrenal (HPA) system, which, in turn, can result in impaired mental health disorders [ 14 , 15 ]. Environmental factors affecting telomere length include age-dependent decrease in RTL [ 8 ], specificity of child–parent relations [ 16 ], adverse traumatic events in childhood [ 15 ], stressful life effects [ 17 ], environmental influence [ 18 ], and the level of family income [ 19 ].…”
Section: Introductionmentioning
confidence: 99%